Organization principles of dynamic three-dimensional genome architecture associated with centromere clustering states - Satya Dev Polisetty; Shuvadip Dutta; Rakesh Netha Vadnala; Dimple Notani; Ranjith Padinhateeri; Kaustuv Sanyal (Proceedings of the National Academy of Sciences, 2025)
Fungal centromeres are clustered near microtubule organizing centers to help adopt the Rabl chromosomal organization. The role of centromere clustering in driving large-scale changes in structural and functional chromatin assembly remains unclear. Here, using Hi-C and superresolution microscopy, we show that cell cycle-dependent centromere declustering and clustering states in Cryptococcus neoformans drive global changes in the 3D genome architecture. Centromeres and telomeres are scattered around the nuclear periphery at interphase G1 , and this arrangement constrains the interarm interactions within a chromosome, providing a unique interphase G1 chromosome organization. Moreover, centromeres and telomeres are organized as separate compartments, segregating them from active euchromatic regions. Polymer modeling reveals that the transition from the unclustered to clustered centromere state during the cell cycle involves changes from a globular to an elongated chromosome architecture. Strikingly, while clustered centromeric regions replicate early in most yeasts, C. neoformans centromeres replicate late in S-phase, hinting at a possible link between centromere clustering dynamics and CEN DNA replication timing. Overall, our study uncovers several unique organizational principles governing the dynamic genome architecture in an evolutionarily diverged basidiomycete yeast.